Multi-wavelength observations and modeling of a microflare: constraining non-thermal particle acceleration - Polito, Vanessa; Peterson, Marianne; Glesener, Lindsay; Testa, Paola; Yu, Sijie; Reeves, Katharine K.; Sun, Xudong; Duncan, Jessie (Frontiers in Astronomy and Space Sciences, 2023)
In this work we analyze a small B-class flare that occurred on April 29 2021 and was observed simultaneously by the Interface Region Imaging Spectrograph (IRIS) and the Nuclear Spectroscopic Telescope Array (NuSTAR) X-ray instrument. The IRIS observations of the ribbon of the flare show peculiar spectral characteristics that are typical signatures of energy deposition by non-thermal electrons in the lower atmosphere. The presence of the non-thermal particles is also confirmed directly by fitting the NuSTAR spectral observations. We show that, by combining IRIS and NuSTAR multi-wavelength observations from the corona to the lower atmosphere with hydrodynamic simulations using the RADYN code, we can provide strict constraints on electronbeam heated flare models. This work presents the first NuSTAR, IRIS and RADYN joint analysis of a non-thermal microflare, and presents a self-consistent picture of the flare-accelerated electrons in the corona and the chromospheric response to those electrons.